A survey of denitrifying Azospirillum brasilense in two contrasted conditions of the sugarcane cropping region of Tucumán, Argentina - Pedraza, Raúl Osvaldo (2012)
The aim of this work was the assessment of denitrifying Azospirillum brasilense isolates in two contrasted regions in the sugarcane cropping region of Tucumán, Argentina. For that, Azospirillum was isolated from the rhizoplane of sugarcane plants using nitrogen-free malate semisolid medium. Microbiological characteristics and restriction profiles of 16S rDNA indicated the presence of A. brasilense. PCR analysis of the isolates showed that the key enzyme for denitrification corresponded to the nitrite reductase type nirS. There were differences among the isolates in their physiological response to the nitrite reductase activity and the enzymatic restriction profiles of the nirS fragment. Differences among the isolates at genomic level were also assessed by RAPD method. According to the higher naturally occurrence of denitrifying Azospirillum in the wetter area of the sugarcane cropping region, our results suggest the existence of an influence of rainfall regime and soil characteristics in their environmental distribution. The knowledge of the ecology of denitrifiers (in this case, Azospirillum strains), represents a step forward to the rational utilization of microbial diversity in agriculture.